2009
DOI: 10.3329/jsr.v2i1.2769
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effects of the Different Fractions of Ethanolic Extracts of <i>Ocimum sanctum</i> in Normal and Alloxan Induced Diabetic Rats

Abstract: The antidiabetic effects of Ethyl acetate (Et-Ac), Petroleum-ether (Pet-ether), and Chloroform fractions from ethanolic extract of the leaves of Ocimum sanctum were investigated in normal and alloxan induced diabetic rats (AIDRs). The effect of these fractions (200 mg/kg body weight i.p) on fasting blood glucose (FBG), total cholesterol (TC), triglyceride (TG), serum glutamate oxaloacetate transaminases, serum glutamate pyruvate transaminases (SGOT, SGPT) level, and liver glycogen content were investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…Results of this study confirmed that gentamycin at a dose of 100 mg/kg body weight produced significant hepatotoxicity as evidenced by which elevated activities of plasma ALT, AST and decrease level of albumin following gentamycin administration is in agreement with earlier studies [21] . AST presents two isoezymes, one located in the cytoplasm and the other in the mitochondria.…”
Section: Discussionsupporting
confidence: 80%
“…Results of this study confirmed that gentamycin at a dose of 100 mg/kg body weight produced significant hepatotoxicity as evidenced by which elevated activities of plasma ALT, AST and decrease level of albumin following gentamycin administration is in agreement with earlier studies [21] . AST presents two isoezymes, one located in the cytoplasm and the other in the mitochondria.…”
Section: Discussionsupporting
confidence: 80%
“…Our previous work also reported hypertriglyceridemia and hyperlipidemia in AIDRs [14]. The ethanol extracts from cucumber, white pumpkin and ridge gourd significantly decreased serum cholesterol level in AIDRs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The liver tissues collected from sacrificed rats were analyzed for glycogen content by UV spectrophotometric method using o-toluidine reagent diagnostic kits as we have reported previously [14]. Briefly, this test utilizes the o-toluidine-glucose-coupling reaction for the estimation of glycogen after trichloroacetic acid (TCA) extraction, precipitation by alcohol and hydrolysis.…”
Section: Estimation Of Glycogen Content In Livermentioning
confidence: 99%
“…21 Therefore, the mechanism underlying the anti-hyperglycemic effect of this plant is partly due to the chemical compositions such as essential oil, alkaloids or flavonoids presence in H. cordata. In the present study, the extract from H. cordata also showed the antihyperlipidemic effect as HCE significantly reduced CHO and TG which were increased in the diabetic control rats.…”
Section: Discussionmentioning
confidence: 99%